THE EFFECT OF INFORMATION SERVICES TO REDUCE STUDENT SMOKING HABITS - Dina Hidayati Hutasuhut (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2018)
The purpose of this study was to determine the effect of information services to reduce smoking habits. The subjects of this study were students of class VIII.5 totaling 35 students. This will be seen in the pre-test that will be done first. The instrument used was a questionnaire to capture data on students who smoked and tested to find out the validity and reliability of the questionnaire. Instruments are given before and after the provision of information services. The data analysis technique uses a different test (t test). The validity test in the questionnaire instrument that is shared with students can be declared valid, because the results of r count > r table are 0.335> 0.334. The results showed that the provision of information services had an effect on reducing smoking habits. It is clear that, t test with the results of t count > t table is 8,417 > 1,697. Based on the results of the t test there is a significant positive effect in the provision of information services to reduce smoking habits in class VIII YP. Nurul Hasaniah Private Middle School, it is acceptable.